Étudiants, sitters, nouchi et bakoroman - Muriel Champy (Ateliers d'Anthropologie)
Firstly, this contribution offers successive accounts of three ethnographies concerning “young people”, in Burkina Faso (Jacinthe Mozzocchetti, 2008, Être étudiant à Ouagadougou : itinérances, imaginaire et précarité), in Gambia (Paolo Gaibazzi, 2015, Bush Bound: Young Men and Rural Permanence in Migrant West Africa) and in the Ivory Coast (Sasha Newell, 2012, The Modernity Bluff: Crime, Consumption and Citizenship in Côte d’Ivoire). Secondly, a comparative parallel is drawn between these three books, with a view to formulating a few hypotheses on the implicit contours of “youth” that are sketched in them. Divided into recurring themes like political mobilisation, waiting and mobility, it shows that, far from only being a question of age, youth presents itself as an implicitly male category, which is designated as such only when it acquires a certain sociopolitical visibility and oppositional firepower.Finally, based on the author’s research among young people living on the streets in Burkina Faso (bakoroman), this article concludes by observing the “young” category’s recent intrusion into Burkina Faso’s political scene, to the point that a re-transcription of vernacular language seems to be asserting itself in the “zenna” written form.